2008
DOI: 10.1371/journal.pone.0002637
|View full text |Cite
|
Sign up to set email alerts
|

Oct-4 Expression Maintained Cancer Stem-Like Properties in Lung Cancer-Derived CD133-Positive Cells

Abstract: CD133 (prominin-1), a 5-transmembrane glycoprotein, has recently been considered to be an important marker that represents the subset population of cancer stem-like cells. Herein we report the isolation of CD133-positive cells (LC-CD133+) and CD133-negative cells (LC-CD133−) from tissue samples of ten patients with non-small cell lung cancer (LC) and five LC cell lines. LC-CD133+ displayed higher Oct-4 expressions with the ability to self-renew and may represent a reservoir with proliferative potential for gen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

11
387
3
3

Year Published

2010
2010
2020
2020

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 444 publications
(404 citation statements)
references
References 44 publications
(53 reference statements)
11
387
3
3
Order By: Relevance
“…12 In our previous study, we demonstrated that nonsmall cell lung cancer (NSCLC)-derived CD133-positive cells displayed higher octamer-binding transcription factor 4 (Oct-4) expression and possessed the ability to self-renew, potentially representing a reservoir of proliferative potential to generate lung cancer cells. 13 Consistent with our findings, Bertolini et al also provided evidence that CD133-positive lung tumor cells possessed stemness features and a higher tumorigenic potential than CD133-negative cells in severe combined immunodeficient (SCID) mice. 14 A growing body of evidence indicates the tumor initiation ability and chemoradioresistance of CD133-positive cells in lung CSCs.…”
supporting
confidence: 92%
See 1 more Smart Citation
“…12 In our previous study, we demonstrated that nonsmall cell lung cancer (NSCLC)-derived CD133-positive cells displayed higher octamer-binding transcription factor 4 (Oct-4) expression and possessed the ability to self-renew, potentially representing a reservoir of proliferative potential to generate lung cancer cells. 13 Consistent with our findings, Bertolini et al also provided evidence that CD133-positive lung tumor cells possessed stemness features and a higher tumorigenic potential than CD133-negative cells in severe combined immunodeficient (SCID) mice. 14 A growing body of evidence indicates the tumor initiation ability and chemoradioresistance of CD133-positive cells in lung CSCs.…”
supporting
confidence: 92%
“…14,28 Our previous results demonstrated that CD133-positive cells isolated from patients with NSCLC exhibit greater chemoradioresistance compared with NSCLC cells of the CD133-negative lineage. 13 To further explore other possible characteristics of CSCs in CD133-positive cells from patients with lung cancer, we isolated CD133-positive cells (Fig. 1A) in tissue samples from 7 patients with NSCLC using the magnetic bead method ( Table 1).…”
Section: Isolation and Characterization Of Lungmentioning
confidence: 99%
“…Most Oct-4 + cells expressed the catalytic subunit of human telomerase (hTERT) [43] (Supplementary information, Figure S1, 1-3) and the cancer stem cell-related markers CD133 [15] (Supplementary information, Figure S1, 5-7), CD24 [44] (Figure 2B, 13-15), CD271 (nerve growth factor receptor p75) [45], as well as βIII tubulin [46], c-kit and nestin [47,48] (Figure 2A). hTERT, CD133, CD24, nestin and CD271 were expressed in different proportions also by Oct-4 − tumor cells (81% ± 4%, 85% ± 2%, 71% ± 4%, 33% ± 2% and 66% ± 5%, respectively, Figure 2A).…”
Section: Identification and Immunophenotypic Characterization Of Oct-mentioning
confidence: 99%
“…The Octamer-binding transcription factor 4 (Oct-4), together with SOX-2 and NANOG, maintains self-renewal and blocks cell differentiation in embryonic stem cells [12][13][14] and is expressed by some cancer stem cells [15][16][17][18][19][20]. Among these factors, Oct-4 and SOX-2 appear to be indispensable for stemness maintenance [21].…”
Section: Introductionmentioning
confidence: 99%
“…Based on down-regulated ROS stress and cell cycle progression in NIH3T3 cells, E-cancer cells, etc., and facilitating differentiation and apoptosis induced by quercetin in our previous experiments (Gong et al, 2009;Zhang et al, 2007), we found that the natural flavonoid quercetin could persist cell ROS in certain normal level, not only to down-regulate ROS to cells with higher ROS level, but also to up-regulate ROS to cells with lower ROS level. There are some anti-CSC studies in breast, leukemia and glioma tumors induced by green tea polyphenol, curcumin, resveratrol and other polyphenols (Chen et al, 2008;Charpentier et al, 2014). However, the information about quercetin anti-CSC effects in human esophageal stratified squamoous epiththelial cancer has been limited.…”
Section: Anti-csc Effects In Human Esophageal Squamous Cellmentioning
confidence: 99%